Variability of Kerguelen-Davis Oscillation Index (KDOI) effecting environmental ecosystem in the Prydz Bay region, east Antarctica - Mikio, Naganobu; Kunio, Kutsuwada; Yoriko, Arai; Hiroto, Murase; Koji, Matsuoka (2013)
第4回極域科学シンポジウム 個別セッション：[OB] 生物圏 11月12日（火） 国立国語研究所 ２階講堂 conference object